2008
DOI: 10.1007/s00428-008-0601-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for optimizing pathologic staging of sentinel lymph nodes in breast cancer patients

Abstract: Due to the extensive pathologic evaluation of the sentinel lymph node (SLN), micrometastases are frequently observed. If micrometastases are clinically relevant, the histopathologic examination of SLNs should be sensitive enough to detect them. The probability of detecting micrometastases was calculated when examining the SLN according to the current Dutch pathology protocol and strategies evaluated to optimize the chance of detection. The dimensions of 20 consecutive axillary SLNs in patients with cT1-2N0 bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…6,15 In our study, this ra ti o was 2.2%. Ve ro ne si re por ted n-SLN me tas ta sis in 35-67% of the ca ses with SLN me tas ta sis.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…6,15 In our study, this ra ti o was 2.2%. Ve ro ne si re por ted n-SLN me tas ta sis in 35-67% of the ca ses with SLN me tas ta sis.…”
Section: Discussionsupporting
confidence: 41%
“…It was lo wer than the values reported in the li te ra tu re. 15 It may depend on the ex pe ri en ce of the sur ge on and the patho lo gist, fro zen sec ti on ar te facts and se ri al sec ti on in ter val and thick ness in per ma nent sec ti ons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have found that MM are clinically relevant, to miss detection of MM is unwanted. Using H&E staining, Madsen et al [27] have suggested that the interval between the sections must be decreased to 200 lm, and 20 levels from each of a bisectioned lymph node must be investigated to detect micrometastasis with a 95% probability. Accepting such a labor-intensive method in the routine laboratory may, however, not be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Kesit aralıklarının 200 μm'u geçmemesi önerilmektedir (46). Kendi kurumumuzda 25 µm aralıklar ile 9 ince kesit alınıp, dokunun büyüklüğüne göre lamlara yerleştirilmektedir.…”
Section: Metastaz Saptanmayan Lenf Düğümlerinin İşlemealınmasıunclassified